Subtle variation of stereo-electronic effects in rhodium(I) carbonyl Schiff base complexes and their iodomethane oxidative addition kinetics. Issue 17 (24th August 2020) - Mokolokolo, Pennie P.; Brink, Alice; Roodt, Andreas; Schutte-Smith, Marietjie
Abstract: Rhodium(I) carbonyl complexes of the form [Rh I ( N, O -ScBa)(CO)(PR3 )] (R = Ph or Cy), with N, O -ScBaH a mono anionic bidentate Schiff base ligand, 2-(cyclopentyliminomethyl)-5-methylphenol (5-Me-Sal-CyPH), and bearing different phosphine ligands on Rh(I), are reported. N, O -ScBaH was also varied to be 2-(cyclohexyliminomethyl)phenol (Sal-CyH) and 2-(isopropyliminomethyl)-5-methylphenol (5-Me-Sal-IPropH) to investigate the effects of different substituent groups on the periphery of the Schiff bases on metal center reactivity. The structural characterization of two sample complexes is described and an extensive spectroscopic kinetic-mechanistic study utilizing UV/vis, infrared and 31 P NMR spectroscopy of the iodomethane oxidative addition is presented. Iodomethane oxidative addition led exclusively to Rh III -alkyl complexes as final products, while an associative activation is inferred from the large negative Δ S ≠ value. The relative reactivity of the [Rh I ( N, O -ScBa)(CO)(PR3 )] complexes when stepwise varying PR3 (PPh3, PPh2 Cy, PPhCy2 and PCy3 ) as tertiary phosphine ligands follow a surprising similar reactivity relationship as observed for a range of isostructural [Rh I ( X, O -Bid)(CO)(PR3 )] complexes, with X = O, N or S in corresponding oxinate, acetylacetonate and thioureate mono anionic X, O -Bid ligands. This suggests systematic and responsive dynamic behavior of the PR3 ligands, independent of the bidentate chelate at the Rh(I) metal center. A variation of more than two orders-of-magnitude in reactivity was observed. Graphical Abstract: